THU0602 Worker productivity loss remains a major issue for patients with inflammatory arthritis and osteoarthritis: results from the international eular-pro worker productivity study. (15th June 2017) - Leggett, S; Bosworth, A; Hoffstetter, C; Boonen, A; Lacaille, D; Mihai, C; Talli, C; Hagel, S; Crepaldi, G; Ramiro, S; Dadoun, S; Verstappen, S; et al.
Abstract : Background: Rheumatic and Musculoskeletal Diseases such as Inflammatory arthritis (IA) and osteoarthritis (OA) are one of the biggest causes of disability and worker productivity loss which has recently been recognized by European policy makers and the World Health Organization (WHO). However, limited information is available about job characteristics and the level of both presenteeism and absenteeism in employed persons with IA or OA across countries. Objectives: To describe job characteristics and worker productivity loss in patients with IA and OA in Europe and Canada. Methods: Patients with IA or OA in paid employment from seven countries within Europe and from Canada were recruited to the EULAR-PRO Worker productivity study. Patients completed a questionnaire including questions about their job, job characteristics and the Work Productivity and Activity Impairment Questionnaire (WPAI) measuring percent hours absent and the percentage their disease affected productivity while working (0–100%=disease completely prevented work). Patients also completed several health-related patient reported outcome measures, including: the Health Assessment Questionnaire (HAQ), Visual Analogue Scale (VAS) general well-being, and EuroQol-5D (EQ-5D). Results: 503 patients were included in this large international study. Mean (SD) age was 47 (10) years, median [IQR] disease duration 12 [5, 21] years and 94% had IA. 42% had a predominately mentally demanding job, 10% physically demanding job, and 48% a combination; with overall 34% reporting their job being very demanding (see table for country specific results). Respectively 12% and 5% of patients were able to often or always postpone work tasks if need be, whilst, respectively 19% and 51% never or sometimes received help from colleagues which may depend on job/employment type and company size. Twenty-one% of patients reported that they missed time off work due to ill-health in the past week (median [IQR] % time missed due to ill-health 20% [9–50]). Interestingly, a total of 11% were unsatisfied with their current job; and 23% of patients did not disclose their disease to their employer. Conclusions: This is one of the largest international studies investigating worker productivity loss in patients with IA and OA. It highlights the burden of the disease across countries and the importance of increasing awareness of rheumatological conditions in order to prevent presenteeism and long-term sick leave by providing the best available intervention to the individual patient in paid employment. Disclosure of Interest: None declared